2014
DOI: 10.1016/j.ijid.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of measles IgG among HIV-1-infected and uninfected Kenyan adults

Abstract: Summary Despite global efforts to reduce measles incidence, outbreaks continue to occur in developing countries where HIV-1-infected adults represent a vulnerable population. Immunization campaigns have targeted children, although little is known about the levels of measles protection in adult populations in Kenya. The objective of this study was to determine seroprevalence and titers of measles IgG among HIV-1-infected and uninfected adults in Nairobi, Kenya. The presence of anti-measles IgG was measured in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 6 publications
0
13
1
Order By: Relevance
“…In this study, most (> 70%) of the HIV-1 and helminth co-infected individuals appear to have adequate immune protection against measles as confirmed by measles seropositivity. The seroprevalence we observed was lower than that seen in a recent study among a similar population of HIV-1 infected adults in Kenya (96%), as well as a study among HIV-1 infected adults in the UK (93%), and comparable to a study in Mexico (76%) ( Belaunzaran-Zamudio et al, 2009 , Molton et al, 2010 , Merkel et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 60%
“…In this study, most (> 70%) of the HIV-1 and helminth co-infected individuals appear to have adequate immune protection against measles as confirmed by measles seropositivity. The seroprevalence we observed was lower than that seen in a recent study among a similar population of HIV-1 infected adults in Kenya (96%), as well as a study among HIV-1 infected adults in the UK (93%), and comparable to a study in Mexico (76%) ( Belaunzaran-Zamudio et al, 2009 , Molton et al, 2010 , Merkel et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 60%
“…22 Further, the antibody response to measles vaccine was not associated with CD4 count in HIV-infected Zambian children. 37 However, a low CD4 count was associated with both a lower measles antibody concentration and a worse response to revaccination with measles vaccine among HIVinfected children in Central Africa.…”
Section: Discussionmentioning
confidence: 93%
“…[15][16][17][18] Other reports have shown that HIV infection is associated with greater severity of measles disease, 19 higher mortality from measles, 20 and prolonged measles virus shedding. 21 Few studies have addressed the role of HIV infection in measles infection risk among adults and children after infancy: 18,22 one study concluded that measles vaccine-derived antibodies decline more rapidly in HIV-infected adults (n = 48); 23 a further three studies reported finding no difference in measles seropositivity between HIV-infected adults at different stages of disease progression (as measured by CD4 count). [24][25][26] A study among Kenyan adults in Nairobi found no statistical difference in measles IgG seroprevalence and concentration between HIV-infected and HIV-uninfected adults, and concluded that reduced immunity among HIV-infected adults was not a major contributor to measles resurgence in that country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections caused by these three illnesses can be severe in individuals with impaired cell-mediated immunity, including HIV infections [4][5][6]. Little data is available regarding anti-measles, mumps, and rubella antibody levels in vaccinated HIV-infected individuals [7][8][9][10]; and no published data are available in the United States which evaluate the seroprevalence of measles, mumps, and rubella IgG antibodies in HIV-infected children compared with control children. Recent US outbreaks of measles, mumps, and rubella in vaccinated immune-competent children [11][12][13] have raised concerns regarding the risk of immunocompromised HIV-infected children, adolescents, and adults contracting these infections and suffering the complications, which include death.…”
Section: Introductionmentioning
confidence: 99%